Comparison between Vertical-Horizontal and Horizontal-Vertical hybrid constructed wetlands. - A.Rashid, Khasraw; Salh, Qadri Karim (Sulaimani Journal for Pure and Applied Sciences, 2016)
Water pollution cause serious health risk to public. Treating wastewater in allow cost efficient way is necessary for the region. This project was designated to describe the usefulness of macrophytes Typha angustifolia L and Phragmites australis, since this could be an index for its utility as a biological purifier for advanced treatment of wastewater. For this purpose a specific model treatment project was hybrid constructed wetland. Constructed wetlands have become a good alternative to urban wastewater treatments. To achieve higher treatment performances, the HCW has various types. The project consists of several purification treatment units; Storage tanks, pre-sedimentation and two hybrid constructed wetlands. They are designed as (Vertical-Horizontal and Horizontal-Vertical) HCW, along with sand filtration implemented with two local macrophytes (Typha angustifolia and Phragmites australis). Experimental hybrid constructed wetlands contain macrophytes, they have grown for 50 days (the period needed for stabilization and adaptation), and taken untreated and treated wastewater samples twice a month periods from June 15, 2013 until September 15, 2013. Water samples were analyzed to determine the some heavy metals in inlet and outlet HCW. Results showed that the decreases in Iron, Copper, Cadmium and Lead contents in the outlet wastewater treatment in (Vertical-Horizontal) HCW higher decreases than (Horizontal-Vertical) HCW. These results showed the design (Vertical-Horizontal) HCW better than the design (Horizontal-Vertical) HCW to wastewater treatment
Keywords: Wastewater treatment,phytoremediation,environmental pollution,HCW design